Co-operative Stores in the United States - Cummings, Edward (Quarterly Journal of Economics, 1897)
Journal Article Co-Operative Stores in the United States Get access Edward Cummings Edward Cummings Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 11, Issue 3, April 1897, Pages 266–279, https://doi.org/10.2307/1882991 Published: 01 April 1897